2016
DOI: 10.1007/s13277-016-4824-5
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cardia adenocarcinoma microRNA profiling in Chinese patients

Abstract: Gastric cardia adenocarcinoma (GCA), which occurs at the gastroesophageal boundary, is one of the most malignant types of cancer. Over the past 30 years, the incidence of GCA has increased by approximately sevenfold, which has a more substantial increase than that of many other malignancies. However, as previous studies mainly focus on non-cardia gastric cancer, until now, the mechanisms behind GCA remain largely unknown. MicroRNAs (miRNAs) have been shown to play pivotal roles in carcinogenesis. To gain insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
“…-5p)[39][40][41][42][43][44][45][46] ; gastric cancer (miR-374b-5p, miR-200c-3p, miR-18b-5p, miR-196a-5p, miR-21-5p, and miR-20a-3p)[47][48][49][50][51] ; ovarian cancer (miR-141-5p, miR-182-5p, miR-483-3p, and miR-200c-3p)[52][53][54][55] ; hepatocellular carcinoma (miR-135a-5p, miR-187-3p, miR-148a-5p, miR-200a-3p, and miR-9-3p)[56][57][58][59] ; colorectal cancer…”
mentioning
confidence: 99%
“…Previous studies showed that miR-3196 is downregulated in basal cell carcinoma [15] and in breast cancer patients with lymph node metastasis [16], whereas it is upregulated in papillary thyroid carcinoma patients with lung metastases [17]. miR-3196 was reported to be also associated with gastric cardia adenocarcinoma differentiation [18]. In the present study, we showed that miR-3196 is involved in apoptosis in lung cancer cells and inhibits VP-16 induced apoptosis by downregulating PUMA.…”
Section: Discussionmentioning
confidence: 99%
“…The miR‐196a‐5p was correlated with age of CGA onset. Survival analysis revealed that the miR‐135b‐5p expression level was correlated with survival of CGA . Table presents the results obtained from microarray analysis of miRNAs in CGA.…”
Section: Micrornasmentioning
confidence: 99%